Dancing Our Way Beyond Work: Playlists and Zines as Teaching Tools to Imagine a World Without Work - van den Berg, Marguerite; Alakavuklar, Ozan Nadir (Radical Teacher, 2023)
For a Master’s course in Organization Studies, in which we addressed refusals of work, we asked students to suggest songs for a playlist to be assembled as the basis for the creation of a zine in a workshop setting. Based on the Zapatista movement’s slogan "one no, many yeses," we asked students to imagine worlds beyond work and to visualize this in a zine. Contemporary music became a critical pedagogical tool for teaching. It allowed us to go beyond critique and the familiar world of work and organizations, and facilitated an affective, creative, and aesthetic movement towards "many yeses" in the form of a zine to refuse work.